Mentoring for the Revitalization of Village-Owned Enterprises Real Work in Efforts to Improve Community Welfare in Salimbatu Village, Tanjung Palas Tengah District, Bulungan Regency - Trimawan, Anang; Adji, Widwi Handari; Rinaldie, Irfan (Yayasan Azka Hafidz Maulana, 2025)
As a village economic institution, the Village-Owned Enterprise (BUMDes) has a very important role in advancing the village economy and community welfare, but what happens if the BUMDes institution is inactive, as experienced by BUMDes Karya Nyata in Salimbatu village, this BUMDes has been inactive since 2022 due to a lack of human resource capacity and administration.. This study aims to determine the effectiveness of BUMDes mentors in efforts to revitalize the Karya Nyata Village-Owned Enterprise (BUMDes), to improve the welfare of the community in Salimbatu village. This mentoring is carried out by PT. Pesona Khatulistiwa Nusantara (PT PKN), as one of the Community Empowerment Programs (CEP) by involving students mentored by PT PKN to become BUMDes mentors through the MBKM program